Structural and Semantic Features of English Terminology (Global Scientific Review, 2022)
This article is devoted to the study of the structural and semantic features of the English-language terminological units that function in modern English. The article is based on the principles of the theory of terminological nomination. The paper highlights the main terminological types and their structural and grammatical features. The causes of synonymy and polysemy of these terminological units are revealed